Phytopharmacology and Clinical Updates of Berberis Species Against Diabetes and Other Metabolic Diseases - Belwal, Tarun; Bisht, Aarti; Devkota, Hari Prasad; Ullah, Hammad; Khan, Haroon; Pandey, Aseesh; Bhatt, Indra Dutt; Echeverría, Javier (Frontiers in Pharmacology, 2020)
Diabetic mellitus and other metabolic diseases are increasing worldwide with lesser available treatments. A more research on the plant extract and derived compounds in both preclinical and clinical studies showed promising results. The plants belonging to genus Berberis (Family: Berberidaceae), which is highly distributed worldwide with nearly 550 species, showed various positive effects against metabolic syndromes. Among various bioactive compounds found in Berberis, an alkaloid, berberine was found to be the main compound responsible for majority of its bioactivity against diabetic and other metabolic syndrome. Various pharmacological experiments were conducted to evaluate the effects of Berberis extracts, berberine and its chemically synthesized derivatives against various cell and animal disease models, and results revealed positive effects. The pharmacological effects were mainly due to modulation of signaling pathways, enzyme activities and cell sensitivity, which are discussed in the present review. Various clinical trials also showed preventive activity of Berberis extract and berberine against metabolic syndromes, however more future concerns are needed related to their safety and long term effects. The present review discusses the research updates on phytopharmacology and clinical studies of Berberis and their active metabolites in prevention and treatment of diabetic and other metabolic syndrome. Further, the review will help in getting more insights on its mechanism of action against metabolic syndromes and also highlight the gaps and possible future works.